SCHOOL-BASED SUPERVISION AND SCHOOL PERFORMANCE IN SECONDARY SCHOOLS OF GURAGE ZONE SNNPR STATE - DABESA, ETECHA FEKADU; FEKADU, SHIREYE CHERAMLAK (Innovare Journal of Social Sciences, 2024)
The purpose of this study was to assess school-based supervision and school performance in secondary schools of Guraghe Zone. To conduct this study, a correlational research design was employed. One Zonal and three District Education Office supervision coordinators were selected through the availability sampling technique. Among the 77 government secondary schools found in the Zone, 10 of them were selected randomly as sample schools. From these sample schools, 10 principals and 10 school-based supervisors (10 unit leaders and 50 heads of department) were also included as respondents using the availability sampling technique. Furthermore, 286 teachers have participated in the study through purposive and availability sampling techniques. Questionnaires and document analysis were tools for collecting data in the stud. Frequency, percentage, mean, and t-test were utilized to analyze quantitative data gained through the questionnaires. The qualitative data gathered through document analyses were by narration. The results of the study indicated that teachers lack awareness and orientation on the activities and significance of school-based supervision, ineffectiveness of the practice of supervisory options matching with the individual teacher’s developmental level, and the inability of supervisors to apply the necessary procedures for classroom observation properly. This all was due to the following factors influencing such as lack of relevant training programs for supervisors, scarcity of experienced supervisors in school-based supervision activities, lack of supervision manuals in the schools, and shortage of allocated budget for supervisory activities, and that also leads to low school performance. Finally, to minimize the problems of school-based supervision and low school performance in secondary schools, it is recommended to give relevant in-service training for supervisors to upgrade their supervisory activities, necessary resources such as supervision manuals, and an adequate budget for the success of supervision at the school level were suggested so that schools can perform in a good manner.